2014
DOI: 10.1038/npp.2014.164
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of TREM2 Ameliorates Neuropathology and Rescues Spatial Cognitive Impairment in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Triggering receptor expressed on myeloid cells 2 (TREM2) gene is a recently identified susceptibility gene for Alzheimer's disease (AD), as its low-frequency variants increase the risk of this disease with an odds ratio similar to that of an APOE e4 allele. To date, the expression and biologic functions of TREM2 under AD context remain largely unknown. Using APPswe/PS1dE9 mice, a transgenic model of AD, we showed that TREM2 was upregulated in microglia during disease progression. For the first time, we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
232
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(247 citation statements)
references
References 38 publications
13
232
2
Order By: Relevance
“…Therefore, it remains unknown if, and to what extent, complete depletion of TREM2 affects Aβ catabolism. Interestingly, overexpression of TREM2 in a mouse model of AD afforded protection against AD progression through the modulation of microglia functions (Jiang, et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it remains unknown if, and to what extent, complete depletion of TREM2 affects Aβ catabolism. Interestingly, overexpression of TREM2 in a mouse model of AD afforded protection against AD progression through the modulation of microglia functions (Jiang, et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%
“…Genetic depletion studies of TREM2 or DAP12 in primary mouse microglia or the microglial BV2 cell line have demonstrated that pro-inflammatory cytokine levels (including IL-1␤, TNF␣, and IL-6) are significantly increased following co-incubation with bacterial lipopolysaccharide (27), apoptotic neurons (24), or A␤ (50). Overexpression of microglial TREM2, however, suppressed this excessive cytokine production under the same stimulatory conditions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of microglial TREM2, however, suppressed this excessive cytokine production under the same stimulatory conditions (27). Furthermore, TREM2 deficiency has been shown to result in reduced phagocytic activity of apoptotic neurons (24,28,29), A␤ (50,51), and E. coli (51) by microglia. A recent report elegantly demonstrated a direct role for TREM2 in facilitating phagocytosis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…-/-mice did not develop spontaneous demyelination, we wanted to determine (35)(36)(37). Moreover, we found that Trem2 was not expressed in astrocytes or ODC precursors after 4 weeks of cuprizone feeding, while its expression in microglia was elevated (Supplemental Figure 2).…”
Section: Trem2 Is Required For Myelin Debris Removal and Remyelinatiomentioning
confidence: 99%